Influence of Digital Technology Utilization on the Learning Outcomes of Economic Education Students - Ramadian, Naufal; Latief, Jamil; Kamarudin, Novie Kurniasih; Alimudin, Muhamad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to examine the effect of digital technology utilization on the learning outcomes of Economics Education students at the Faculty of Teacher Training and Education, Universitas Muhammadiyah Prof. Dr. Hamka. A quantitative approach with a survey method was employed to collect data from 100 Economics Education students selected using simple random sampling with a 5 percent error level. Data were gathered through a structured questionnaire and analyzed using descriptive statistics and simple linear regression analysis. The results of validity and reliability tests indicate that all research instruments are valid and reliable. The findings reveal that digital technology utilization has a positive and significant effect on students' learning outcomes, as evidenced by a regression coefficient of 0.623 and a significance value below 0.05. The coefficient of determination shows that digital technology utilization explains 38.8 percent of the variance in learning outcomes. These results suggest that the effective use of digital technology contributes meaningfully to improving academic performance in Economics Education learning. The study highlights the importance of integrating digital technology pedagogically to enhance learning effectiveness in higher education.